Challenges and Strategies for Inventory Management in Small and Medium-Sized Cosmetic Enterprises: A Review - Kittisak, Arthit (International Journal of Information Technology and Computer Science Applications, 2023)
This research paper presents a case study analysis of the inventory management challenges faced by small and medium-sized cosmetic enterprises (SMEs) and the strategies employed to overcome them. The study was conducted through qualitative research methods, including in-depth interviews with managers of SMEs in the cosmetics industry. The findings revealed that the major challenges faced by SMEs in managing their inventory were poor demand forecasting, inadequate storage facilities, and lack of efficient inventory control systems. To mitigate these challenges, SMEs employed strategies such as outsourcing inventory management, adopting technology-driven inventory control systems, and establishing efficient supply chain networks. The study concludes that effective inventory management is crucial for the success of SMEs in the cosmetics industry, and the strategies identified in this study could be useful for practitioners seeking to improve their inventory management practices.